Dextromethorphan Drug Abuse Against Adolescent Learning Concentration: Literature Review - Kori’atun Ni’mah; Joko Sutrisno; Lingga Kusuma Wardani (PT. Griya Eka Sejahtera, 2021)
Background: Dextromethorphan is often misused with excessive doses so that it gives a euphoric effect, a sense of calm, visual and auditory hallucinations. In fact, if taken in the recommended dosage, these pills are useful for suppressing coughs (antitussive) and phlegm-busting. However, it is often misused as a drug pill, because if you take too much, at least 10 pills at a time, it can cause nervous system depression that can become addictive. This study aimed to explore the abuse of the dextromethorphan class of drugs on adolescent learning concentration. Method: the researcher used a literature review design. The method used in the literature review is through a systematic approach to analyze data in a simplified approach. The keywords in this study are dextromethorphan drug abuse and concentration in learning. Results: Dextromethorphan is often misused with excessive doses so that it gives a euphoric effect, a sense of calm, visual and auditory hallucinations. Dextromethorphan intoxication or overdose can cause hyperexcitability, fatigue, sweating, slurred speech, hypertension, and can cause respiratory depression. Conclusion: Dextromethorphan drug abuse is associated with tolerance, addiction or addiction problems which can then develop into drug dependence (drug dependence). Students who experience deviant behavior in the form of drug abuse of the dextromethorphan class will experience impaired concentration while studying.